2017
DOI: 10.1007/s00701-017-3431-6
|View full text |Cite
|
Sign up to set email alerts
|

Single-stage total resection of giant dumbbell-shaped hypoglossal schwannoma: a case report

Abstract: Extensive large dumbbell-shaped hypoglossal schwannoma is extremely rare, and total resection is nearly impossible. We present a case of a 61-year-old male with a giant-size hypoglossal schwannoma with moderate tongue atrophy. The tumor extended from the enlarged hypoglossal canal to the brainstem intradurally and the high cervical region extradurally. Through the extreme lateral infrajugular transcondylar (ELITE) skull base approach, the tumor was totally removed in a single-stage operation. Single-stage tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Jiang et al [ 11 ] also reported the use of occipitocervical fusion in 6 patients (1.7%) after cervical laminectomy and facetectomy. As regards intraoperative neuromonitoring adjuncts, monitoring on the lower cranial nerves (IX-XII) was used in 22 patients (6.2%) [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ], monitoring of the somatosensory evoked potentials in 17 patients (4.8%) [ 11 , 21 , 42 , 43 , 44 ], monitoring of the motor evoked potential in 16 patients (4.5%) [ 11 , 21 , 42 , 45 , 46 ], and monitoring the brainstem evoked potential in 1 patient (0.3%) [ 38 ]. Similarly, microdoppler assistance was used only by Oichi et al [ 26 ] to detect the relationship of the tumor and the surgical resection to the proximal arterial and venous structures in 1 patient (0.3%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jiang et al [ 11 ] also reported the use of occipitocervical fusion in 6 patients (1.7%) after cervical laminectomy and facetectomy. As regards intraoperative neuromonitoring adjuncts, monitoring on the lower cranial nerves (IX-XII) was used in 22 patients (6.2%) [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ], monitoring of the somatosensory evoked potentials in 17 patients (4.8%) [ 11 , 21 , 42 , 43 , 44 ], monitoring of the motor evoked potential in 16 patients (4.5%) [ 11 , 21 , 42 , 45 , 46 ], and monitoring the brainstem evoked potential in 1 patient (0.3%) [ 38 ]. Similarly, microdoppler assistance was used only by Oichi et al [ 26 ] to detect the relationship of the tumor and the surgical resection to the proximal arterial and venous structures in 1 patient (0.3%).…”
Section: Resultsmentioning
confidence: 99%
“…The high frequency of sensory disturbances likely stems from the sensory nerve roots’ tumor origin, while other impairments are caused by tumors compressing contiguous structures, such as lower cranial nerves (hoarseness, speech disorders, hearing disturbance), cerebellum (ataxia), and brainstem/cervical spinal cord (motor disorders) [ 31 , 36 , 54 ]. Tongue atrophy is typical in hypoglossal schwannomas [ 40 ], while evident neck masses may be found in otherwise asymptomatic slow-growing C1–C2 tumors [ 55 ]. Owing to the frequent multiple cranial neuropathies (27.1%) in our pooled cohort, we suggest performing comprehensive pre-operative neurological and radiological evaluations in patients with suspected CVJ masses to optimize the surgical planning and restore cranial nerves’ functions.…”
Section: Discussionmentioning
confidence: 99%
“…Inoue et al reported a case of 61-year-old male presenting with a one year history of tongue atrophy and dysarthria. 22 Imaging revealed a dumb-bell shaped giant mass in the right extradural hypoglossal canal invading intradurally with a large extension to the high cervical region. The authors used a single-stage radical surgical procedure using the anterolateral extreme lateral infrajugular transcondylar exposure approach.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this typology of dissection reproduces with great reliability the "in vivo" surgical scenario, giving a more detailed idea of the feasibility of a specific surgical approach and making the neurosurgeon more familiar with the "real life" surgical anatomy. [29][30][31][32] Since the HN is commonly compressed or dislocated by CVJ lesions, 16,25 we decided to describe its anatomy by simulating a lateral approach to the CVJ.…”
Section: Discussionmentioning
confidence: 99%